Sistema VLC aplicado ??s redes 5G - Oliveira, Marco Aur??lio de (2020)
This work reports experimental analyses of a visible light communication (VLC) system using the new standard for the fifth generation of mobile networks (5G NR). The proposed system is based on the use of directly-modulated light emitting diodes (LEDs) to transmit signals to line-of-sight free space links. Four optical carriers, from a RGBA (red, green, blue, and amber) LED, were individually evaluated, aiming to deploy a high-throughput system based on different colors. The system performance investigation has been realized in terms of root mean square error vector magnitude (EVMRMS) and as a function of the LED bias currents, link length and throughput. In order to compensate the electric amplifiers non-linear response, the digital pre-distortion (DPD) technique has been implemented in an M-QAM signal. At 75 cm, 872 Mbit/s and 1.92 Gbit/s throughput were obtained with the 5G NR standard and DPD-based MQAM signal, respectively. In addition, a simultaneous transmission of different waveforms has been analyzed using a single access point, with the purpose of enabling multiple technologies in the same indoor environment. Finally, the carrier aggregation concept was proposed and demonstrated in an optical attocell.